Labelling the psychological impact of colour in films for deep learning processing based on the humanities approach: RGB information in colour classification in film - Roh, Hyunjung; Whelan, Thomas; Hwang, Suhyoun; Kim, Minju; Han, Youngsue (JAHR (Rijeka ), 2022)
Inspired by Goethe’s theory of colour and his aversion to Newton’s scientific theories, we performed an experiment to investigate the psychological impact of colour in film. We converted 550 films into sequences of images and then processed them to extract the RGB information within. We then compared this data and matched them to classifications of colour roles in terms of their psychological influence on film viewers. For this we consulted Bellantoni, Patti (2005)’s book If It’s Purple, Someone’s Gonna Die: The Power Of Colour In Visual Storytelling, which is a guide for filmmakers to select the appropriate colours for their films and also describes the psychological and emotional effects of certain colours in film on viewers. Finally we extracted RGB information from our image sequence archives to match them to classifications of the role of colour and their psychological influences on film viewers. In spite of the fact that our results are subject to certain limitations such as the subjectivity of our researchers, we believe our findings from the experiment have made contributions to the development of AI for use in film colour classification with regard to their psychological impacts on viewers. In future endeavors, we expect to include additional information, such as shapes, tints and so on. Thus, our methodology and materials may produce even better results if supplementary resources were to be available. Nadahnuti Goetheovom teorijom boja i njegovom averzijom k Newtonovim znanstvenim teorijama izveli smo eksperiment kako bismo istražili psihološki utjecaj boja u filmovima. Pretvorili smo 550 filmova u sljedove slika i procesirali ih kako bismo iz njih izvukli informacije o RGB modelu. Zatim smo usporedili te podatke i spojili ih s klasifikacijama uloga boja u vidu njihovog psihološkog utjecaja na filmske gledaoce. Za ovo smo se konzultirali s knjigom “Ako je ljubičasto, netko će umrijeti: Moć boja u vizualnom pripovijedanju” (engl. If It’s Purple, Someone’s Gonna Die: The Power Of Colour In Visual Storytelling) (2005) autorice Patti Bellantoni, koja filmašima služi kao vodič za biranje prikladnih boja za njihove filmove. Knjiga također opisuje psihološke i emocionalne utjecaje određenih boja u filmovima na gledaoce. Na kraju smo izvukli informacije o RGB modelu iz naših arhiva sljedova slika kako bismo ih spojili s klasifikacijama uloga boja i njihovog psihološkog utjecaja na filmske gledaoce. Unatoč činjenici da su naši rezultati podložni određenim ograničenjima poput subjektivnosti naših istraživača, vjerujemo da su rezultati našeg eksperimenta pridonijeli razvoju umjetne inteligencije koja se koristi za klasificiranje boja u filmovima u vidu njihovog psihološkog utjecaja na gledaoce. U budućim pothvatima planiramo uključiti dodatne informacije poput oblika, nijansi i sl. Smatramo kako bi naši materijali i metodologija mogli polučiti bolje rezultate kad bi nam bili dostupni dodatni resursi.